(Un)Sanctioned: young adult literature as meaningful sponsor for writing teacher education. Issue 1 (8th April 2019) - Sams, Brandon L.; Cook, Mike P.
Abstract : Purpose: The purpose of this paper is to examine youth literacy and writing practices in select, contemporary young adult literature (YAL), especially how and why literate activity is sponsored, negotiated or occluded by teachers and schools. Design/methodology/approach: The authors position young adult fiction as case studies of youth composing in and out of school. Drawing on Stake's (1995) features of case study research in education, the authors present readings of Gabi, a Girl in Pieces by Isabel Quintero and The Vigilante Poets of Selwyn Academy by Kate Hattemer that highlight particular problems and insights about youth literacy practices that are worth extended examination and reflection. Findings: Both novels feature youth engaging in powerful literacy and writing practices across a range of modes to critically read and write their worlds. These particular texts – and other YAL featuring youth composing – offer teacher educators and pre-service teachers opportunities for critical reflection on their evolving stances on literacy instruction; identities as writing and literacy educators; and pedagogies that enable robust literate activity. Originality/value: In the US educational context, teacher education programs are required to provide pre-service teachers numerous opportunities to observe and participate as teachers in public school classrooms. YAL offers a unique setting of experience that can be productively paired with more traditional field placements to complement pre-service writing teacher education. Reading YAL featuring youth composing can serve as a useful occasion of reflection on pedagogies that limit and/or make possible students' meaningful engagement with words and the world.